Prevention of Mental Health Difficulties for Children Aged 0–3 Years: A Review - Izett, Elizabeth; Rooney, Rosanna; Prescott, Susan L.; De Palma, Mia; McDevitt, Maryanne (Frontiers in Psychology, 2021)
The period of infancy and early childhood is a critical time for interventions to prevent future mental health problems. The first signs of mental health difficulties can be manifest in infancy, emphasizing the importance of understanding and identifying both protective and risk factors in pregnancy and the early postnatal period. Parents are at a higher risk of developing mental health problems during the perinatal period. An understanding of the evidence around prevention and intervention for parental anxiety and depression is vital to the process of prevention of early mental health disorders in infants and young children. Here we review the existing prevention and treatment interventions in the early years focusing on the period from conception to 3 years – the majority targeting parents in order to improve their mental health, and that of their infants. Elements of successful programs for parents include psychoeducation and practical skills training, as well as work on the co-parenting relationship, developing secure attachment, and enhancing parental reflective functioning. While both targeted and universal programs have produced strong effect sizes, universal programs have the added benefit of reaching people who may otherwise not have sought treatment. In synthesizing this information, our goal is to inform the development of integrated models for prevention and novel early intervention programs as early in life as possible.